Analysis of socio medical files of women with pregnancies before they were 15 years old in three Mexican hospitals. Notes to Social Work - Pérez-Baleón, Fabiola (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
This article proposes a double objective, one technical and one academic: 1) To establish some elements to access and systematize statistically the information of socio-medical records collected by the Department of Hospital Social Work. 2) To explore information obtained from the socio-medical records of women with pregnancies before the age of 15, attended during 2017 in three hospitals in Mexico to describe their socioeconomic, educational, and health profile. The women in question made their transition to adult sexual and reproductive life before the age of 15. Most of them had incomplete secondary education, lived in a free union or were single, worked at home, and had had at least five prenatal consultations. 94% of these women were in their first pregnancy; the percentage that had resolved their pregnancies through vaginal deliveries was high; only a few of them had had cesarean or abortions. Once their babies were born, a high percentage used postpartum contraception. Social Workers must be methodical at the time of filling the socio-medical record and systematize the information to propose actions to prevent pregnancies in adolescence. Hospitals should report cases of sexual abuse in pregnant adolescents.